Obstructed labour at Usmanu Danfodiyo university teaching hospital Sokoto: a five-year review - Yakubu, Ahmed; Sagir, Tukur Dabo; Panti, Abubakar A.; A., Garba Jamila; Mani, Isah Usman; Funtua, Anas Rabiu; Chappa, Aliyu Muhammed; Markus, Mbakwe (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Obstructed labour is an obstetric emergency and one of the major causes of maternal and perinatal morbidity and mortality in the developing countries, Nigeria inclusive. The aim of this study was to determine the prevalence, causes and feto-maternal outcome of cases of obstructed labour managed at Usmanu Danfodiyo University Teaching Hospital Sokoto from 1st January, 2014 to 31st December, 2018. Methods: This was a retrospective review of all cases of obstructed labour managed at Usmanu Danfodiyo University Teaching Hospital Sokoto over 5 years. List of cases managed during the study period was obtained and case notes were retrieved. Relevant information such as age, booking status, parity, educational status, address, causes, mode of delivery and both maternal and foetal outcomes were obtained from the case notes. Data analysis was done using statistical package for social sciences version 22 (SPSS Inc, Chicago, IL, USA). Results: A total two hundred and seventy-six cases of obstructed labour were managed out of the 15,452 total deliveries during the study period. This gives an obstructed labour prevalence of 1.79%. The major cause of obstructed labour identified in this study was Cephalopelvic disproportion (74.6%) and majority of the patients were delivered by emergency lower segment caesarean section (70.6%). Up to 32.3% of the patients had no maternal complications and also 42.3% of them had live birth with no fetal complication. However, 20.2% of these patients had ruptured uterus and 37.9% of them had still birth, while 19.8% had live birth complicated by birth asphyxia. Conclusions: This study has found that obstructed labour resulted in adverse maternal and perinatal outcome. Hence, there is need to prevent obstructed labour in order to avert this consequence.